Trametes versicolor glutathione transferase Xi 3, a dual Cys‐GST with catalytic specificities of both Xi and Omega classes. Issue 18 (6th September 2018) - Schwartz, Mathieu; Perrot, Thomas; Deroy, Aurélie; Roret, Thomas; Morel‐Rouhier, Mélanie; Mulliert, Guillermo; Gelhaye, Eric; Favier, Frédérique; Didierjean, Claude
Abstract : Glutathione transferases (GSTs) from the Xi and Omega classes have a catalytic cysteine residue, which gives them reductase activities. Until now, they have been assigned distinct substrates. While Xi GSTs specifically reduce glutathionyl‐(hydro)quinones, Omega GSTs are specialized in the reduction of glutathionyl‐acetophenones. Here, we present the biochemical and structural analysis of TvGSTX1 and TvGSTX3 isoforms from the wood‐degrading fungus Trametes versicolor . TvGSTX1 reduces GS‐menadione as expected, while TvGSTX3 reduces both Xi and Omega substrates. An in‐depth structural analysis indicates a broader active site for TvGSTX3 due to specific differences in the nature of the residues situated in the C‐terminal helix α9. This feature could explain the catalytic duality of TvGSTX3. Based on phylogenetic analysis, we propose that this duality might exist in saprophytic fungi and ascomycetes. Abstract :